Frequency and coexistence of the C677T and A1298C polymorphisms of the MTHFR gene in Aures region of Algeria - DJAARA HAYAT; YAHIA MOULOUD; BOUSSIF ABDELALI (Society for Indonesian Biodiversity, 2018)
Hayat D, Mouloud Y, Abdelali B. 2018. Frequency and coexistence of the C677T and A1298C polymorphisms of the MTHFR gene in Aures region of Algeria. Biodiversitas 19: 1169-1175. The aim of this study was to assess the frequency of the two most common polymorphisms C677T and A 1298C of the methylenetetrahydrofolate reductase (MTHFR) gene, as well as the coexistence of both these genetic variants in healthy subjects from part of the Algerian population (Aures Region). A total of 94 apparently healthy subjects were enrolled in the study group. The frequency of the both investigated genotypes of the both MTHFR gene polymorphisms (C677T and A1298C) was determined by using the Real-Time Polymerase Chain Reaction-Fluorescence Resonance Energy Transfer (Real-Time PCR-FRET) technic. The frequencies of C and T alleles of C677T polymorphism were 127 (67.55%), 61 (32.45%), and for CC, CT, and TT genotypes were 44 (46.48%), 39 (41.8%) and 11 (11.70%) respectively. Regarding the frequencies at position 1298, for A and C alleles were 147 (78.19%), 41 (21.81%), and for AA, AC, and CC genotypes were 60 (63.82%), 27 (28.72%) and 7 (7.44%) respectively. Also, our results indicated that no significant differences in the percentage distributions of the C677T (P=0.518) and A1298C (P=0.514) polymorphisms between males and females carriers. As noted in the findings, the most frequent coexistence of genotypes were 677CT/1298AA (29.78%), 677CC/1298AA (22.34%) and 677CC/1298AC (17.02%%). The coexistence of 677TT/1298AA (11.70%), 677CT/1298 AC (11.70%) and 677CC/1298 CC (7.44%) genotypes was observed less frequently and for 677TT/1298AC, 677CT/1298CC, 677TT/1298CC genotypes, it has been no observed in the studied population. The frequency of MTHFR 677 C and T alleles were 0.66 and 0.31, whereas that of MTHFR1298 A and C alleles were 0.77 and 0.21, respectively. The allelic distributions of the C677T polymorphism remain intermediate in the Aures region (Northeast of Algeria); that support the idea of a north-south gradient. For the A1298C SNP, our funding appears to be lower compared across populations. In addition, the frequency and coexistence of genotypes of the C677T and A 1298C MTHFR gene polymorphisms in the region studied are similar to other ethnic group populations.